(untitled) - Gopal, Krishan (Laxmi Nagar, New Delhi, 2003)
Contents of material: Impact of ICTs in libraries. Role of libraries in digital age. Analysis of digital information services. Digital repositories. Digital preservation. Digital archiving. Electronic library trends. Copyrigh issues.
Keywords: Information technology,Information storage and retrieval systems,Information services